(untitled) (Journal of Engineering, 2006)
This paper deals with the dynamics and stability behavior of a welded pipe containing flowing fluid having a small harmonic component superposed. The equation of motion was derived to represent the motion of a welded pipe conveying a pulsatile flow using a tensioned Euler- Bernoulli beam theory. The finite element analysis was used to simulate the harmonic motion of a welded pipe conveying fluid. It was shown that welded pipes with clamped-clamped and clamped-pinned supports are subject to a multitude of parametric instabilities in all their modes. Stability maps are presented for parametric instabilities of welded pipe with clamped-clamped and clamped-pinned ends. It is found that the extent of the instability regions increases with flow velocity for clamped-clamped and clamped-pinned welded pipes. The most important consideration from a practical point of view is to avoid the onset of parametric resonance.